PSCArs2294008 T polymorphism increases the risk of bladder cancer in Bai, Dai, and Han ethnicity in China and a potential mechanism - Yang, Junfeng; Li, Wei; Zhang, Zhuorui; Shen, Jie; Zhang, Ningnan; Yang, Min; Yang, Maolin; Yu, Yanhong (Genes & genomics, 2018)
The aim of this study is to make a comparative evaluation on association of PSCArs2294008 C/T polymorphism with the risk of bladder cancer in Bai, Dai, and Han people in China. A potential mechanism of the T allele risk was also investigated. T allele increased the occurring risk of bladder cancer in Han (OR 1.34; 95% CI 1.17–1.69), Dai, (OR 1.33; 95% CI 1.12–1.70), and Bai (OR 1.14; 95% CI 1.08–1.57) people. T genotype was also observed to associate with invasive bladder cancer in all the three populations (Bai, OR 1.15, 95% CI 1.07–1.87; Dai, OR 1.17, 95% CI 1.05–2.23; Han, OR 1.22, 95% CI 1.10–2.09). PSCA m-RNA levels in T genotype bladder cancer tissues were significantly lower than those in C genotype. An enhancement of PSCA m-RNA level by over-expressing C or T genotype in bladder cancer cells both decreased the cell proliferation and migration, but not affected cell cycle. The increased cell apoptasis due to the over-expression of the two variants was observed. Those change of cell proliferation, migration, and apoptasis was more remarkable in over-expressed C genotype cells than those in over-expressed T genotype. T genotype was genetically high risk to the occurrence of bladder cancer. The decreased PSCA m-RNA levels were involved in the progress of bladder cancer. T allele takes more responsibility for PSCA m-RNA down-regulation to promote cell proliferation and migration and hinder cell apoptasis, thus leading to a higher risk.